Doprowadż następujące wyrażenia do prostszej postaci:
a) (x+y)²-(x-y)²+
b) (x+4)²+4(x-1)²=
c) 3(2-y)²+4(y-5)²=
d) 5(3-5a)²-5(3a-7)(3a+7)=
e) (m+1)²+3(m-1)²-5(m+1)(m-1)=
f) (a-1)²-4(a+1)²-6(a+1)(a-1)=
g) -(3+x)²+5(1-x)²-3(1-x)(1+x)=
h) (x-2)(x+2)-(x-3)²+(x+1)²=

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-10-28T18:25:02+01:00
A) (x+y)²-(x-y)² = x²+2xy+y²-x²+2xy-y² = 4xy
b) (x+4)²+4(x-1)² = x²+8x+16+4x²-8x+4 = 5x²+20
c) 3(2-y)²+4(y-5)² = 12-12y+3y²+4y²-40y+100 = 7y²-52y+112
d) 5(3-5a)²-5(3a-7)(3a+7) = 45-150a+125a²-45a²-245 = 80a²-150a-200
e) (m+1)²+3(m-1)²-5(m+1)(m-1) = m²+2m+1+3m²-6m+3-5m²+5 = -m²-4m+9
f) (a-1)²-4(a+1)²-6(a+1)(a-1) = a²-2a+1-4a²-8a-4-6a²+6 = 9a²-10a+3
g) -(3+x)²+5(1-x)²-3(1-x)(1+x) = -9-6x-x²+5-10x+5x²-3+3x² = 7x²-16x-7
h) (x-2)(x+2)-(x-3)²+(x+1)²= x²-4-x²+6x-9+x²+2x+1 = x²+8x-12
2009-10-28T22:42:44+01:00
B) = x²+4²+4x²-4²=5x²
c) = 6²-y²+4y²+20²=36+3y²+400=436+3y²